Real estate markets and macroprudential policy in Europe - Philipp Hartmann (European Central Bank (ECB), 2015)
Boom-bust cycles in real estate markets have been major factors in systemic financial crises and therefore need to be at the forefront of macroprudential policy. The geographically differentiated nature of real estate market fluctuations implies that these policies need to be granular across regions and countries. Before the financial crisis that started in 2007 property markets were overvalued in a range of European countries, but much like in other constituencies active policies addressing this were an exception. An increasing number of studies suggest that borrower-based regulatory policies, such as reductions in loan-to-value or debt-to-income limits, can be effective in leaning against real estate booms. But many of the new macroprudential policy authorities in Europe do not have clear powers to determine them. Moreover, the cross-border spillovers they may give rise to suggest the establishment of a well-defined macroprudential coordination mechanism for the single European market.
Keywords: G01; G28; R39; G17; E5; 330; bubbles; financial crises; financial regulation; financial stability indicators; macroprudential policy; real estate markets; systemic risk